STUDI PEMANFAATAN JENIS BAMBU OLEH MASYARAKAT DAYAK BAKATI DI HUTAN ADAT DESA TANJUNG KECAMATAN TERIAK KABUPATEN BENGKAYANG - Junisa, Junisa; Oramahi, H A; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2019)
The purpose of this study was to obtain data on the types of bamboo used by the community and study the patterns of bamboo utilization by the people of Tanjung Village, Teriak District, Bengkayang Regency. The research was conducted in Tanjung Peninsula Village Teriak District Bengkayang Regency Â± 4 weeks effective in the field. The tools used include location maps, GPS, herbarium equipment (alcohol, plastic packing, newspapers, scissors, insulation and hanging labels), cameras, questionnaires, tally sheets, recording devices, gloves, machetes, knives and cuttings. The method used is a survey and observation method with direct interview techniques. Sampling is done by using purposive sampling. Based on data obtained at the study site, 10 types of bamboo were utilized by the people of Tanjung Village, Teriak District, Bengkayang Regency, which were found are (Bambusa multiplex), (Bambusa vulgaris), (Dendracalamus asper), (Dendrocalamus hirtellus), (Gigantochloa ater), (Gigantochloa balui), (Gigantochloa hasskarliana), (Gigantochloa levis), (Schantz brachycladum), (Schzostachyum flexuosum). All types of bamboo are used in the from of craft (13 kinds of utilizion), consumption (3 kinds of utilizion), ritual costoms (7 kinds of utilizion), medicine (2 kinds of utilizion) and farming implements (15 kinds of utilizion).Keyword: Bamboo, Tanjung village, Utilization, Community forest